Relación entre la Motivación y Rendimiento Académico en Estudiantes de Décimo Grado de una Institución Educativa Oficial del Municipio de Ciénaga Magdalena, Colombia (2023)
Motivation is a key factor for students to be able to perform and apply their skills and achieve the proposed goals of the designed plan of the educational institution, the motivation variable raised in the research can be related, which is essential to carry out the different activities when acquires said motivation, the student acquires responsibility, the relationship that this has with academic performance being very significant. The research was carried out with a quantitative approach, taking into account the type of variable and the elements adopted by the investigation, collecting the data of the current academic performance, performance of the tests to know and the results of the questionnaire test for the motivation of the students. students of the educational institution, performing the Pearson correlation, a significant correlation was presented as a result between motivation and academic performance with a significance of 0.7, which indicates that the greater the motivation, the better the academic performance of the students. students, and with the performance of tests to know, motivation does not present such a strong relationship, being 0.4. The findings obtained are relevant since they allow us to know the importance of motivation in the academic performance of students, since motivation is necessary for the student to set a goal to meet, it is the key variable that leads to better performance. academic, that is, it is beneficial, it produces in students reflection, innovation and at the same time a change of attitude, becoming a conscious being